If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9(x-1)=3(3-x)+6x
We move all terms to the left:
9(x-1)-(3(3-x)+6x)=0
We add all the numbers together, and all the variables
9(x-1)-(3(-1x+3)+6x)=0
We multiply parentheses
9x-(3(-1x+3)+6x)-9=0
We calculate terms in parentheses: -(3(-1x+3)+6x), so:We get rid of parentheses
3(-1x+3)+6x
We add all the numbers together, and all the variables
6x+3(-1x+3)
We multiply parentheses
6x-3x+9
We add all the numbers together, and all the variables
3x+9
Back to the equation:
-(3x+9)
9x-3x-9-9=0
We add all the numbers together, and all the variables
6x-18=0
We move all terms containing x to the left, all other terms to the right
6x=18
x=18/6
x=3
| 4x-3(5x-9)=4-x | | 3n^2+37n=1360=0 | | 2(x+1)+3(x*2)=x+3 | | 2q^2=37q+60 | | x+(0.5)x=24 | | 5x+10=3x=60 | | X-5/6=2x+1/3 | | 2x-9-5x=-6x+8-4x+3 | | 5*n+6=n | | x/(1/30)=(5/10) | | 7(x-2)=3x=46 | | 5/x=30/18 | | 2b-6=90 | | X^2+12x+4X=0 | | 0.4x-0.6=0.3+7 | | 54-(2x+3)=5(x+7)+x | | 14y=255-2y | | 2b+(6-b)=90 | | 1.3x+67.1=4.1-9.2x | | 7.3√x=3(√x+8.06)-4.59 | | 8/3x+1/3x=5x+44/3+5/3x | | d+11=6 | | 1/6(4t-8)=t+8/12 | | F(x)=x5 | | 12x-13=17x-13 | | 836.50=6.50x+2.00x | | y(6y+7)=3 | | 3x+7-6(x+1)=5x+6 | | 0.9=1.7*(1-x)-7.1*x | | 7x-24/6x=1/2 | | z/87=6 | | 5(x-2)=6(x+4) |